Siri’ To Tuo : Resiproritas Dalam Budaya Mappassolo’ Di Desa Bajiminasa Kabupaten Bulukumba - Firzah Aurelia; Andi Ima Kesuma (Rayhan Intermedia, 2023)
This study aims to elaborate on exchange practices that occur in the people of Bajiminasa Village which are carried out through the mappassolo culture. Data collection techniques were obtained through observation, interviews and documentation involving several informants. The results of this study indicate: (1) The forms of exchange that occur in the 'mappassolo' culture in Bajiminasa village are very helpful to the community, especially event owners, both socially and economically. (2) There is a change in the community's meaning of the values contained in the reciprocity of the mappassolo culture, but does not reduce the values contained in this culture. (3) the people of Bajiminasa Village related to their siri' philosophy have a feeling of obligation for them to return what they have received because this is the same as a debt for them and must be paid back.